From COVID-19 to global health: challenges and opportunities in mRNA vaccine manufacturing - Choudhary, Varun; Mehta, Anirudh; Niaz, Moazam; Sohoni, Aditya Pradeep; Dave, Pooja; Nwagwu, Urenna; Samad, Abdul (Frontiers in Virology, 2026)
Messenger RNA (mRNA) vaccines have emerged as a powerful tool in combating infectious diseases, including COVID-19, by synthesizing and delivering bioactive mRNA molecules that must remain stable and functional to transcribe target genes and effectively enter host cells. This review provides a brief examination of the synthesis and purification processes of mRNA vaccines, their formulation strategies, production scalability, regulatory frameworks, and global supply chain systems. Several challenges—including molecular instability during synthesis and lipid nanoparticle encapsulation, reliance on specialized equipment, insufficient supply of raw materials and skilled labor, and the need for standardized production quality at scale—are underscored. These concerns are further compounded by fragmented regulatory approval processes and the complexity of maintaining cold chain logistics, particularly in low-resource settings. Addressing these barriers is essential, and emerging solutions include integrating automation and artificial intelligence to enhance manufacturing efficiency and reduce associated costs. Additionally, ongoing research aims to improve the environmental stability of mRNA vaccines, thereby reducing reliance on cold storage and increasing accessibility in developing countries. Prospective developments further encompass the globalization of regulatory standards, the concentration of production capacities, and the application of mRNA technology beyond infectious diseases, including cancer and hereditary disorders. Overall, the review emphasizes that resolving manufacturing and logistical challenges together with international cooperation and supportive policy frameworks is crucial for advancing a new era of mRNA-based therapies accessible to populations worldwide.